Comprehensive evaluation of the response to aluminum stress in olive tree (Olea europaea L.) - Niu, Erli; Gao, Song; Yu, Xiaomin; Soleimani, Ali; Zhu, Shenlong (Frontiers in Plant Science, 2022)
Olive (Olea europaea L.) is an ancient tree species in the Mediterranean, but the lack of knowledge about aluminum-resistant varieties limits its introduction in acidic soil. Here, the seedlings of 97 olive germplasms with 1.0~3.0 cm roots and 2 leaves were chosen to treat with 50 µM Al3+ (pH = 5.0). By factor analysis of the traits of defoliation rate, rooting rate, length of extend root and length of new root, 97 germplasms were classified into five different groups according to their diverse responses to aluminum stress, including highly resistant (5, 5.15%), medium resistant (30, 30.93%), general (31, 31.96%) and medium sensitive (23, 23.71%) and highly sensitive (8, 8.25%). The top three highly sensitive and highly resistant germplasms were further employed for the metabolomics and transcriptomics analyzes. Exposed to aluminum stress, 96 differentially accumulated metabolites (DAMs)/4845 differentially expressed genes (DEGs) and 66 DAMs/2752 DEGs were identified in highly sensitive and resistant germplasms, respectively. With multi-omics technology, the pathways and related DAMs/DEGs involved in the cell wall/cytoplasm receptor, ROS balance, hormone induction, synthesis of organic acids, Al3+ transport and synthesis of metabolites were identified to mainly regulate the response to aluminum stress in olive. The study will provide the theoretical guide and prior germplasms and genes for further genetic improvement of the aluminum tolerance in olive tree.